2014
DOI: 10.1590/s1517-83822014000200048
|View full text |Cite
|
Sign up to set email alerts
|

Improved 1-Deoxynojirimycin (DNJ) production in mulberry leaves fermented by microorganism

Abstract: DNJ, an inhibitor of α-glucosidase, is used to suppress the elevation of postprandial hyperglycemia. In this study, we focus on screening an appropriate microorganism for performing fermentation to improve DNJ content in mulberry leaf. Results showed that Ganoderma lucidum was selected from 8 species and shown to be the most effective in improvement of DNJ production from mulberry leaves through fermentation. Based on single factor and three factor influence level tests by following the Plackett-Burman design,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…DNJ can be isolated from mulberry ( Jiang et al, 2014 ; Wang et al, 2014 , 2015 ; E et al, 2017 ; Hu et al, 2017 ) or produced by Bacillus species ( Lee et al, 2013 ; Seo et al, 2013 ; Do et al, 2015 ; Cai et al, 2017 ). DNJ may be a potential drug for treating post-prandial hyperglycemia with few side effects ( Asai et al, 2011 ; Jiang et al, 2014 ). With the study on DNJ, it has been found to have many health promoting properties.…”
Section: Introductionmentioning
confidence: 99%
“…DNJ can be isolated from mulberry ( Jiang et al, 2014 ; Wang et al, 2014 , 2015 ; E et al, 2017 ; Hu et al, 2017 ) or produced by Bacillus species ( Lee et al, 2013 ; Seo et al, 2013 ; Do et al, 2015 ; Cai et al, 2017 ). DNJ may be a potential drug for treating post-prandial hyperglycemia with few side effects ( Asai et al, 2011 ; Jiang et al, 2014 ). With the study on DNJ, it has been found to have many health promoting properties.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also reported the effectiveness of mulberry leaves in skin aging [49,50] and neurodegenerative disorders including Alzheimer’s disease and Parkinson’s disease [51]. Moreover, sedative effect of mulberry fruits and anti-inflammatory, diuretic, antitussive, and antipyretic properties of mulberry root bark have been studies [52]. In addition to DNJ, many other bioactive compounds including flavonoids, alkaloids, steroids, and coumarins also exist in mulberry leaves [53].…”
Section: 1-deoxynojirimycinmentioning
confidence: 99%
“…The recovery and purity of DNJ in the end product were >90% and >15%, respectively [62]. Jiang et al stated that fermentation of mulberry leaf by Ganoderma lucidum produced the highest DNJ content [52]. The optimal condition for mulberry fermentation, obtained from RSM, was the following: pH 6.97, potassium nitrate content 0.81%, and inoculums volume 2 mL.…”
Section: 1-deoxynojirimycinmentioning
confidence: 99%
“…1-Deoxynojirimycin (DNJ), a natural alkaloid from plant mulberry or microorganism, is a conventional hypoglycemic drug in clinical application for effectively inhibiting α -glucosidase activity [ 7 , 8 ]. Thus, it could potently inhibit the metabolism of saccharides and lower blood glucose levels.…”
Section: Introductionmentioning
confidence: 99%